UMA FENOMENOLOGIA DAS INTERVENÇÕES CLÍNICAS COM ARTE E INTERAÇÃO HUMANO-ANIMAL EM NISE DA SILVEIRA. - SILVA, Bruna Guimarães de Sousa e (2020)
This dissertation aims to carry out a study of the clinical interventions of Nise da Silveira at Pedro II Hospital, carried out through artistic expression and Human-Animal Interaction, and their intersections with phenomenology, in order to outline their contributions to Clinical Phenomenological Psychology in the contemporary life-world. It starts from the perception that Nise's differentiated approach in the clinic, valuing respect for her clients and for a posture free of prejudices towards them, can be seen from the phenomenological point of view. This dissertation traces the path of Nise’s approach, starting with the explanation of her biography. Then, a brief history of artistic expression on the treatment in psychiatric hospitals and in the studio opened at Hospital Pedro II is presented, also reflecting on the importance of mandalas and abstraction in the works created. Considering the relevance of the life-world of Nise's clients, a discussion on the trajectory of some of them, as examples of the possibilities of resignifying the senses in clinical interventions, follows. Soon after, Human-Animal Interaction, and the role of co-therapists in therapeutic performance, are discussed. Finally, the phenomenological attitude is approached in parallel with Nise’s way of acting in the clinic, dealing with its contributions to the phenomenological clinic through such an attitude, and the catalyzing affection characterized by intersubjectivity. The research was developed as a theoretical study, through the phenomenological method. The final reflections show activity, affection and freedom as pillars of Nise's interventions, reflecting on how the phenomenological attitude of suspension of a prioris generates learning in the clinic and also the creation of new ways of seeking with the client, their own possibilities for improvement, thus emphasizing ethics, and the inseparability of subject/object as essential for clinical and also scientific performance.